Durability of Antibody Responses to SARS-CoV-2 Infection and Its Relationship to Disease Severity Assessed Using a Commercially Available Assay - Alshami, Alanoud; Al Attas, Rabab; Anan, Hadeel; Al Maghrabi, Aroub; Ghandorah, Salim; Mohammed, Amani; Alhalimi, Abdulbary; Al-Jishi, Jumana; Alqahtani, Hadi (Frontiers in Microbiology, 2021)
Background: Assessing the humoral immune response to SARS-CoV-2 is crucial for inferring protective immunity from re-infection and for assessing vaccine efficacy. Data about durability and of SARS-C0V-2 antibodies carry conflicting messages. In this study, we aimed to determine the seroconversion rate of SARS-CoV-2 infection among a cohort of reverse-transcriptase polymerase chain reaction (RT-PCR)-confirmed SARS-CoV-2 infection and the dynamics of antibodies, durability, and the correlation of antibody titters with disease severity using commercially available SARS-CoV-2 anti-spike (S1/S2) protein. Methods: A total of 342 subjects with PCR confirmed COVID-19 were enrolled. A total of 395 samples were collected at different time points (0-204) after onset of symptoms or from the day of positive PCR in asymptomatic patients. Demographics, clinical presentation and the date of PCR were collected. All of the samples were tested using the automated commercial chemiluminescent assay Results: The seroconversion rate was 65.2%. The rate of seroconversion in symptomatic patients (62.1%) was similar to that of the asymptomatic patients (56.1%) p =(0.496). The IgG titters distribution was also similar across both groups (p = 0.142) with median IgG levels of 27.86 (3.8–85.5) and 15 (3.8–58.85) in symptomatic and asymptomatic patients, respectively. However, IgG titters were significantly higher among ICU patients with a median of 104 Au/ml (3.8–179) compared to 34 Au/ml (3.8–70) in the non-ICU patients (p < 0.0001). Furthermore, the median time to seroconversion was significantly lower in ICU patients compared non-ICU patients (19 versus 47 days) (P < 0.0001). IgG titters were also higher in subjects ≥50 years compared to < 50 years (p <.009), Male compared to Female (p< .054) and Non-Saudi compared to Saudi (p<. 003). Around 74% of all samples tested beyond 120 days were positive. Conclusion Majority of patients with COVID-19 mounted humoral immune responses to SARS-CoV-2 infection that strongly correlated with disease severity, older age and male gender. However, a subgroup of patients who are non-seroconverts exists . The implication of this findings on reinfection need to be further evaluated in future studies. Majority of patients tested beyond 120 days had persistent antibodies indicating that natural immunity can last more than 4 months